Body height robust control of automotive air suspension system using finite‐time approach. Issue 2 (15th June 2021) - Yin, Chunfang; Zhao, Dean; Zhang, Jun; Wang, Shaohua; Xu, Xing; Sun, Xiaoqiang; Shi, Dehua
Abstract: One of the essential characteristics of electronically controlled air suspension (ECAS) is that the automotive height is adjustable. Because ECAS system has complex nonlinearity and noticeable hysteresis, it is easy to make the vehicle oscillate near the target height due to the overcharge/discharge of air springs, which would cause the instability of vehicle body posture. More than that, the existence of external disturbances and uneven loads has impacts on body height control. The complex nonlinear characteristics and the existence of external interference put forward higher requirements for the design of ECAS body height controller. In this paper, by non‐singular coordinate transformation, the nonlinear model of the 1/4 ECAS body height regulation system is transformed into a linear model with a third‐order integral chain firstly, which is closer to the real dynamic characteristics of the suspension system than the linear system with low order. Secondly, based on continuous finite‐time theory, a continuous finite‐time feedback stabilization controller with small parameters is designed, and it turned out that the height regulation system can achieve finite‐time stability. Finally, the simulation results under sinusoidal and random disturbances show that with the comparison with the traditional PD control, the designed finite‐time controller can not only guarantee the system faster response speed and better control accuracy but also obtain the better anti‐jamming performance. By innovatively applying the finite‐time theory to the ECAS system, the designed control system in this paper can afford good robustness for ECAS height adjustment and has great significance to improve the overall performance of ECAS system.